A detailed experimental parametric analysis of bolted and hybrid bolted/bonded composite joints. Issue 5 (17th November 2022) - Li, Xin; Xu, Bo; Hong, Yang; Luo, Haibo
Abstract: Hybrid bolted/bonded joints may have the advantages of both mechanical and adhesively bonded joints or disadvantages, which depends entirely on reasonable design. The design of the hybrid bolted/bonded joint is a complex issue, which is related to the material properties of the connected parts and adhesive layer, the number and size of the bolt, and the geometrical characteristics of the joint. Furthermore, the secondary bending in the single‐lap joint and the bypass load in the multirow bolted joint to increase the complexity of the problems. Therefore, detailed tests and adequate data are essential to do further research on the mechanical behaviors of bolted and hybrid bolted/bonded composite joints, especially for the joints of bismaleimide resin composite. An experimental parametric study was carried out to reveal the effect mechanisms of different configurations on the mechanical properties of bismaleimide resin composite joints in this study. Single‐lap bolted and hybrid bolted/bonded composite joints were focused on and their mechanical behaviors were discussed. According to the investigation of experimental analysis, some useful conclusions have been deduced, which are helpful for the design of bolted and hybrid bolted/bonded composite joints. Abstract : The effect mechanisms of different configurations on CF/BMI composite joints.